History + Resources = A Sense of Place - Griswold, Wendy (Maine Policy Review, 2002)
Unlike many states, Maine has an unusually strong “sense of place,” or cultural regionalism. Wendy Griswold explores where this unusually strong sense comes from, and how it can be further nourished through literature. In doing so, she strengthens the argument for investments in cultural-heritage objects and activities as a means not only of reinforcing an already strong sense of identity among Mainers, but also of promoting Maine as a tourism destination.
Keywords: Maine; sense of place; regional culture